Bali Brunch Restaurant: Collaboration Is a Recipe For Starting Indonesian Restaurant Business In Competitive Amsterdam - Trian Angga Pradipta; Meitolo Hulu; Shiela Riezqia (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2023)
This study examines Bali Brunch Restaurant’s strategic efforts of collaboration with multistakeholders to survive in a competitive environment in Amsterdam. Amsterdam is a touristic European city that is already packed with many Indonesian restaurants and other restaurants– its competitors. Bali Brunch, established in 2022, is a newcomer in restaurant industry in Amsterdam and need a survival strategy in starting its business. This research is based on argument that Bali Brunch is commencing operations in Amsterdam with an innovative concept: collaborating with artistic individuals to create something entirely novel. This partnership introduces a burst of novelty to the restaurant industry, seamlessly integrating creative elements into the dining experience. Bali Brunch tries to establish a setting that goes beyond mere sustenance by collaborating with imaginative individuals, combining the essence of Bali's culture with the vibrant atmosphere of Amsterdam. In addition to this impressive teamwork, Bali Brunch is also implementing intelligent marketing strategies. They are employing a shrewd tactic to distinguish themselves in the thriving culinary landscape. By utilising intelligent advertisements and exclusive promotions, their aim is to become the preferred destination for both residents and tourists. Through the combination of innovative collaboration and strategic marketing, Bali Brunch is poised to become the premier destination for a brunch experience that deviates from the ordinary. This research is conducted with a descriptive qualitative approach with primary and secondary data collection. Primary data collection is derived from interviews and observations to Bali Brunch Restaurant, whereas secondary data is carried out through the collection of documents related to online and offline research studies.